Cultivating Uncultured Bacteria from Northern Wetlands: Knowledge Gained and Remaining Gaps - Dedysh, Svetlana N. (Frontiers in Microbiology, 2011)
Northern wetlands play a key role in the global carbon budget, particularly in the budgets of the greenhouse gas methane. These ecosystems also determine the hydrology of northern rivers and represent one of the largest reservoirs of fresh water in the Northern Hemisphere. Sphagnum-dominated peat bogs and fens are the most extensive types of northern wetlands. In comparison to many other terrestrial ecosystems, the bacterial diversity in Sphagnum-dominated wetlands remains largely unexplored. As demonstrated by cultivation-independent studies, a large proportion of the indigenous microbial communities in these acidic, cold, nutrient-poor and water-saturated environments is composed of as-yet-uncultivated bacteria with unknown physiologies. Most of them are slow-growing, oligotrophic microorganisms that are difficult to isolate and to manipulate in the laboratory. Yet, significant breakthroughs in cultivation of these elusive organisms have been made during the last decade. This article describes the major prerequisites for successful cultivation of peat-inhabiting microbes, gives an overview of the currently captured bacterial diversity from northern wetlands and discusses the unique characteristics of the newly discovered organisms.